Ответы и объяснения

2013-03-31T01:30:48+04:00

   =   3 - 2х -8 + х     =  - х -5        =  -    (х+5)     =    -1     

           х² -25              (х-5)(х+5)       (х-5)(х+5)          х-5

 

= у²+30+6-12 у   =  у² - 12у  +36   =    (у-6)²   =  у-6

     у-6                         у-6                          у-6

 

2(3-в) + в(2-9в)   =   6-2в+2в-18в²    =   6-18в²     = 6(1-3в²)   =   1-3в²

              6в⁴                          6в⁴                       6в⁴                  6в⁴             в⁴

 

= (х+5)(х-2) - (3х-10)  = х²+3х-10-3х+10 =  х²

           х-2                             х-2                      х-2

 

= х(х+2у)            +   2у²         х         -   2у²         ху-2у²   =   у(х-2у)  =   1

   (х-2у)(х+2у)         у(2у-х)      (х-2у)       у(х-2у)       у(х-2у)        у(х-2у)